2021
DOI: 10.3390/rs13193977
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Attitude Determination Using Single-Difference Observables Based on Multi-Antenna GNSS Receiver with a Common Clock

Abstract: A global navigation satellite system (GNSS) receiver with multi-antenna using clock synchronization technology is a powerful piece of equipment for precise attitude determination and reducing costs. The single-difference (SD) can eliminate both the satellites and receiver clock errors with the common clock between antennas, which benefits the GNSS short-baseline attitude determination due to its lower noise, higher redundancy and stronger function model strength. However, the existence of uncalibrated phase de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…From the results of the attitude solution, the normal high attitude correction for the instantaneous sea surface height on our designed buoy was within 1 cm (Figure 12), while a small amount of correction exceeding 1 cm existed, but these higher corrections were not based on the attitude angle corrected from the normal solution, but were due to the unfixed ambiguity in the dynamic baseline solution process leading to the error in the attitude angle solution [35,36]. (3) After correcting the tidal data of the GNSS buoy using the attitude angle measured by the multi-antenna GNSS, the tidal measurement accuracy was only improved by 0.3 mm compared to the pre-correction values, and similar problems have been…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…From the results of the attitude solution, the normal high attitude correction for the instantaneous sea surface height on our designed buoy was within 1 cm (Figure 12), while a small amount of correction exceeding 1 cm existed, but these higher corrections were not based on the attitude angle corrected from the normal solution, but were due to the unfixed ambiguity in the dynamic baseline solution process leading to the error in the attitude angle solution [35,36]. (3) After correcting the tidal data of the GNSS buoy using the attitude angle measured by the multi-antenna GNSS, the tidal measurement accuracy was only improved by 0.3 mm compared to the pre-correction values, and similar problems have been…”
Section: Discussionmentioning
confidence: 95%
“…From the results of the attitude solution, the normal high attitude correction for the instantaneous sea surface height on our designed buoy was within 1 cm (Figure 12), while a small amount of correction exceeding 1 cm existed, but these higher corrections were not based on the attitude angle corrected from the normal solution, but were due to the unfixed ambiguity in the dynamic baseline solution process leading to the error in the attitude angle solution [35,36]. (3) After correcting the tidal data of the GNSS buoy using the attitude angle measured by the multi-antenna GNSS, the tidal measurement accuracy was only improved by 0.3 mm compared to the pre-correction values, and similar problems have been encountered by scholars in previous studies [37], which occurred for two reasons: first, because the wobble angle of the buoy itself is not large (−10 • ~10 • ), and the second is that the distance of the main antenna of the GNSS buoy from the center of the buoy was very short (0.61 m), which, under the combined influence of these two factors, leads to a small amount of attitude correction for the GNSS buoy, which was not prominent in the tidal extraction process.…”
Section: Discussionmentioning
confidence: 95%
“…Previous works have investigated the advantages of the SD model over the DD model with a common-clock receiver. It is found that with respect to the DD model, the achievable baseline accuracy of the SD model in the vertical could be improved to the same level as the horizontal, and the accuracy of pitch and roll could be improved to the same level as for yaw [8,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these phase LBs therefore prevents the SD integer ambiguity resolution (AR). One way to tackle this problem is parameter reorganization, which is simple to implement but only DD ambiguities are resolved [8,14]. An alternative approach is first calculating and filtering the phase LBs over time and then correcting them with the SD model, in which the DD and SD models are utilized simultaneously [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [13] proposed a single-difference (SD) approach to retain the advantages of SD observables and a one-step ambiguity substitution technique to separate ambiguities from SD uncalibrated phase delay. The proposed method was validated in both static and kinematic modes, and the results were consistent with the reference attitude data.…”
mentioning
confidence: 99%